Rekonstruksi Soal Fisika Berbasis HOTS Menggunakan Metode CFA pada Ujian Sumatif Kelas XI SMA - Amalia, Rizki; Sulisworo, Dwi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2023)
This research aims to analyze and apply the reconstruction results of evaluation instruments in the form of HOTS-based physics questions using the CFA method in the Class XI SMA Summative Examination. The method used in the research is quantitative using a descriptive approach. The discussion in this article is part of the steps of HOTS-based Summative Exam question reconstruction research. The results of this study show that the HOTS content in class XI physics summative questions in high school is 50%, consisting of C4 and C5. There are also questions that contain 50% LOTS consisting of C1, C2 and C3. The reconstructed HOTS base question indicators contain a HOTS cognitive level of 100% with the aim of equipping and familiarizing students with thinking analytically, critically and creatively and being able to compete in the world of national and even international education.